D2.4 Self-diagnostic analysis for sustainability - Loureiro, S. M. C. (2022)
Online tool which allows the self-diagnosis concerning the sustainable practices in place. These months from the beginning of the project until October 2022 have been dedicated to the process of conducting the literature review, using a systematic and bibliometric approach. This step is important to start to develop the tool self-diagnostic on sustainability. The objective of this tool is to allow the self-diagnosis concerning the sustainable practices in place (e.g., water waste, energy saving, carbon emissions). The stakeholders that will use this tool are the SMEs involved in the Resetting project. This tool has the functionality of being used by SMEs to allow them to analyze themselves how they are doing in terms of sustainability, even after the project has been accomplished.